Intimate partner violence, social support, and depression among women living with HIV in Wakiso District, central Uganda: findings from a sequential mixed-methods study - Joan Nalunkuuma; Deborah Ojiambo; Joanita Nangendo; Fred C. Semitala; Samuel Ouma (BMC, 2026)
Abstract Background Intimate partner violence (IPV) remains a pervasive public health concern, disproportionately affecting women worldwide and posing significant risks to their physical and psychological well-being. Women living with HIV (WLHIV) are particularly vulnerable to IPV though both its extent or nature and impact on mental wellbeing of WLHIV in Uganda have not been extensively examined. The aim of this sequential explanatory mixed-methods study was to examine the association between intimate partner violence, social support, and depression in WLHIV in central Uganda. Methods We sampled 215 for the quantitative strand. The Abusive Behaviour Inventory (ABI), Beck Depression Inventory (BDI) and Multi-Dimensional Scale of Perceived Social Support measured IPV, depression and social support respectively. These were followed by individual face-to-face semi structured interviews with a subsample of 10 women. Descriptive frequencies, Pearson correlations and process macro were analyzed in SPSS software while interviews were analyzed thematically. Results Overall, 15.1% experienced IPV, 24.9% were depressed respectively, and 68.4% had moderate to high perceived social support as well as significant negative correlations between IPV and depression. Social support significantly mediated the relationship between IPV and depression. Qualitative results explained the earlier quantitative results under three main themes: (1) Multiple forms of Violence/Abuse (2) Managing and Coping with Violence/abuse.3) Impact of Violence/abuse. Conclusion Addressing IPV, promoting social support and financial independence can enhance efforts aimed at ART adherence and improving mental health outcomes among vulnerable WLHIV.
Keywords: Intimate partner violence; Social support; Depression; HIV/AIDS; Women and sequential mixed methods